Carbon dioxide, membrane potential and intracellular potassium activity in frog skeletal muscle. - Huguenin, F (1980)
1. The membrane potential of isolated frog muscle fibres has been measured in absence and in presence of CO2, at constant external pH. 2. At a normal external Cl concentration, CO2 (PCO2 = 97 mmHg; pH = 7.0) applied for 10 min caused a highly variable depolarization, the average potential change being 8 mV after 5 min. The effect was reversible 3. In Cl-free solutions, CO2 (PCO2 = 97 mmHg; pH = 7.0) caused a biphasic depolarization of 20 mV after 5 min. The effect was fully reversible on CO2 removal. 4. The same effect appeared at a lower partial pressure (PCO2 = 38 mmHg; pH 7.3) in the presence of tetrodotoxin (10(-7) M). 5. In order to investigate the cause of the CO2-induced depolarization, membrane potential and intracellular K activity (ai/K,)( of surface muscle fibres were measured with voltage and ion-sensitive micro-electrodes. 6. At a normal external Cl concentration, CO2(PCO2 approximately equal to 97 mmHg; pH = 7.0) decreased ai/K by 5 mM after 5 min. 7. The same effect appeared at low external Cl concentration (11 mM). 8. At high partial pressure (PCO2 approximately equal to 588 mmHg; pH = 6.8), CO2 reduced ai/K by 19 mM in 10 min. 9. In long-term experiments performed over 4 h with a normal external Cl concentration, CO2 (PCO2 approximately equal to 97 mmHg; pH 5.8 or 7) changed practically neither membrane potential, nor ai/K. 10. It is concluded that increasing the PCO2 when keeping the external pH constant causes an early depolarization of muscle. This effect is particularly marked in the absence of chloride. It can be explained partly, in surface muscle fibres, by a decrease of the intracellular K activity.